Pengaruh Integrasi Artificial Intelligence (AI) dalam LKPD Pembelajaran IPA terhadap Motivasi Belajar Siswa Sekolah Dasar - M. Misbachul Huda; Maulana Paramaditya Ananta; Nur Laili Maghfirothi (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2026)
Generation Alpha, the cohort currently dominating elementary education, has grown up entirely within a digital ecosystem, resulting in learning characteristics that favor interactive, personalized, and technology-based experiences, including those involving Artificial Intelligence (AI). This condition demands instructional innovation in science (IPA) education that can address the learning needs of this digital generation while enhancing student motivation, given that research directly integrating AI into Student Worksheets (LKPD) for elementary science instruction remains scarce. This study aimed to analyze the effect of using AI-integrated worksheets on the learning motivation of elementary school students in science instruction. A quantitative approach with a quasi-experimental method using a Posttest Only Nonequivalent Control Group Design was employed, involving 45 students in an experimental group who received AI-integrated worksheets and 45 students in a control group who received conventional worksheets. Learning motivation data were collected through a 30-item Likert-scale questionnaire and analyzed using the Shapiro-Wilk normality test, Levene's homogeneity test, an Independent Samples t-Test, and Cohen's d effect size. The results showed that the experimental group's learning motivation scores were significantly higher than those of the control group, with an effect size classified as large. It can be concluded that integrating AI into science worksheets has a positive and significant effect on the learning motivation of elementary school students, positioning it as a viable instructional innovation aligned with the learning characteristics of Generation Alpha.